Implementation of an Online Learning Module for Health Care Providers to Improve Discussions About Weight Gain with Pregnant Women (FS16-01-19). (13th June 2019) - Graham, Jocelyn; Bell, Rhonda; Bondariazadeh, Dolly; Miller, Terri; Burnett, Chloe
Abstract: Objectives: This study evaluated the uptake, satisfaction and intentions of health care providers (HCP) after completing an accredited online learning module focused on how they can support women in achieving a healthy diet, physical activity and appropriate gestational weight gain (GWG). Methods: Alberta Health Services, University of Calgary, and the ENRICH Research team partnered to launch an accredited e-learning module in June 2018, aimed at HCP (MDs, nurses, RDs, others) involved in perinatal care in Alberta. The aim of the module is to improve HCP knowledge and strategies for discussing healthy GWG and related behaviours with pregnant women. Results were obtained in Dec 2018 from an evaluation survey assessing participants' perceived changes in knowledge, skills (5-point Likert scale) and intentions (open-ended questions) to incorporate new strategies into their practice in the next 3 months as a result of completing the module. Results: By Dec 2018, 216 people had registered for the module (70 MDs (40%), 61 RNs (28%), 31 RDs (14%) and 54 others); 80 (38%) had completed the module and 77 (96%) of them submitted the evaluation survey Mean satisfaction rating was 4.42/5. Self-assessment of knowledge and skills also increased after completing the module. Registrants reported that the case scenarios and inclusion of tools and resources were important (mean rating 4.2 and 4.1 respectively) components of the module. The majority of registrants found the module easy to navigate and information was appropriate to their learning needs. Most completers agreed (31/77) or strongly agreed (44/77) that they learned something in the module that they will incorporate into practice. Registrants reported that they intended to: improve their counselling strategies (21; by using empowering, client-centred language), use a tool mentioned in the module (11), improve patient education opportunities (8), and find ways to support a collaborative approach to prenatal care (7). Conclusions: The module appears to positively impact self-reported knowledge of healthy pregnancy weight gain concepts and counselling skills. Supporting health care providers to have effective discussions with pregnant women about lifestyle and GWG is an important step towards better compliance with recommendations and improving perinatal outcomes. Funding Sources: Funding was provided through a Collaborative Research and Innovation Opportunity (CRIO) Program grant from Alberta Innovates as part of the ENRICH research program.